Ukrainian Language in Ukrainian Schools of Trans-Dnieper Ukraine during the Central Rada: Dreams or Reality - Kachur, Alina (Pedagogical Discourse, 2012)
Through epoch of national revival this article shows us brightly educational politics of Central rada, the fight of social-pedagogical workers who wanted to set Ukrainian language as learning subject and as basic language of school management.